The Role of Flipped Classroom Strategies on English Speaking Ability: A Systematic Literature Review - Aditia, Gilang Rizkia; Arum, Titis; Ilu, Notburga Astriviana (Electronic Journal of Education, Social Economics and Technology, 2025)
This study aims to examine the role of flipped classroom strategies in enhancing learners’ English speaking ability within the context of English as a Foreign Language (EFL) through a Systematic Literature Review (SLR) approach. The review follows the PRISMA 2020 guidelines and the PICOS framework to synthesize empirical studies published between 2021 to 2025. Literature searches were conducted across major academic databases, including Scopus, Web of Science, ERIC, and Google Scholar. 234 articles initially identified, 37 peer-reviewed and reputable studies met the inclusion criteria and were analyzed thematically. The synthesis of findings indicated that the implementation of flipped classroom approaches consistently yields positive effects on EFL learners’ speaking ability, particularly in terms of fluency, oral performance, confidence, reduced speaking anxiety, and willingness to communicate. Improvements in pronunciation were also reported. However, these outcomes appear to be context-dependent and are strongly influenced by the quality of instructional design, feedback mechanisms, and the duration of the intervention. In addition, several recurring challenges in implementing flipped classroom models were identified, including limited access to technology, learners’ readiness for autonomous learning, increased teacher workload, and time constraints. Overall, the findings suggested that the effectiveness of flipped classroom approaches in English speaking instruction is determined more by pedagogical alignment and learning context than by the use of technology alone. This study offers practical implications for EFL practitioners and highlights directions for future research on sustainable and context-sensitive flipped classroom implementation.KEYWORDS: Flipped classroom; English speaking ability; EFL learners; Speaking instruction; Oral communication